Pengolahan Sampah Plastik Polypropylene (PP) Menjadi Bahan Bakar Minyak Dengan Metode Perengkahan Katalitik Menggunakan Katalis Zeolit X - Ekky Wahyudi; Zultiniar Zultiniar; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The objective of this research was to convert a waste plastic into liquid fuel using zeolite X catalyst which it was synthesized from coal fly ash. In this study, 100 grams of polypropylene-type plastic were cracked in a batch reactor at 350 400 and 450o C for 60 minutes with various catalyst/plastic ratios was 0.5; 1.0;1.5 (wt%). Highest yield (%) was 76.09% that obtained at 450o C and catalyst/plastic ratio was 1.5%.Keywords : Cracking, Liquid fuel, Polypropylene, Waste plastic, Zeolite X